Population Structure and Historical Demography of the Oriental River Prawn (Macrobrachium nipponense) in Taiwan - Chen, Po-Cheng; Shih, Chun-Han; Chu, Ta-Jen; Wang, Daryi; Lee, Ying-Chou; Tzeng, Tzong-Der (PLOS ONE, 2016)
The oriental river prawn (Macrobrachium nipponense) is a non-obligatory amphidromous prawn, and it has a wide distribution covering almost the entire Taiwan. Mitochondrial DNA fragment sequences of the cytochrome oxidase subunit I (COI) and 16S rRNA were combined and used to elucidate the population structure and historical demography of oriental river prawn in Taiwan. A total of 202 individuals from six reservoirs and three estuaries were separately collected. Nucleotide diversity (π) of all populations was 0.01217, with values ranging from 0.00188 (Shihmen Reservoir, SMR, northern Taiwan) to 0.01425 (Mingte Reservoir, MTR, west-central Taiwan). All 76 haplotypes were divided into 2 lineages: lineage A included individuals from all sampling areas except SMR, and lineage B included specimens from all sampling locations except Chengching Lake Reservoir (CLR) and Liyu Lake Reservoir (LLR). All FST values among nine populations were significantly different except the one between Jhonggang River Estuary (JGE, west-central Taiwan) and Kaoping River Estuary (KPE, southern Taiwan). UPGMA tree of nine populations showed two main groups: the first group included the SMR and Tamsui River Estuary (TSE) (both located northern Taiwan), and the second one included the other seven populations (west-central, southern and eastern Taiwan). Demographic analyses implied a population expansion occurred during the recent history of the species. The dispersal route of this species might be from China to west-central and west-southern Taiwan, and then the part individuals belonging to lineage A and B dispersed southerly and northerly, respectively. And then part individuals in west-central Taiwan fell back to and stay at estuaries as the sea level rose about 18,000 years ago.